2006
DOI: 10.1002/cphc.200500357
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Properties in the Liquid Phase: Combining High‐Level Ab Initio Calculations and Classical Molecular Dynamics

Abstract: We present an integrated computational tool, rooted in density functional theory, the polarizable continuum model, and classical molecular dynamics employing spherical boundary conditions, to study the spectroscopic observables of molecules in solution. As a test case, a modified OPLS-AA force field has been developed and used to compute the UV and NMR spectra of acetone in aqueous solution. The results show that provided the classical force fields are carefully reparameterized and validated, the proposed appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 70 publications
4
49
0
Order By: Relevance
“…Previous calculations of shielding constants of organic molecules have discussed the model requirements necessary for accurate descriptions. [62][63][64][65] For supermolecular systems, the use of DFT has shown to be a good compromise between accuracy and computational effort [40][41][42][43][44][45]63 allowing the explicit inclusion of several solvent molecules. In this work, we first use the B3LYP ͑Refs.…”
Section: Calculation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous calculations of shielding constants of organic molecules have discussed the model requirements necessary for accurate descriptions. [62][63][64][65] For supermolecular systems, the use of DFT has shown to be a good compromise between accuracy and computational effort [40][41][42][43][44][45]63 allowing the explicit inclusion of several solvent molecules. In this work, we first use the B3LYP ͑Refs.…”
Section: Calculation Detailsmentioning
confidence: 99%
“…5 Recently, the solvent shift of the nuclear magnetic shielding constants of acetone in NW has been the subject of several theoretical studies. [40][41][42][43][44][45] Both ͑ 13 C͒ and ͑ 17 O͒ in vacuum and in NW are negative ͑deshield͒ but the solvent shifts are in opposite directions: the gas-to-NW shift in ͑ 13 C͒ is negative, whereas the gas-to-NW shift in ͑ 17 O͒ is positive. Experimental results 40,46 give gas-to-NW shifts in 13 C and 17 O of −18.5 and 75.5 ppm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, at that point, the precise origin of these differences was unclear and this inspired us to perform a more in-depth analysis. This study followed the procedure as proposed by the group of Barone et al, who demonstrated that averaging over different configurations-generated during an MD simulationleads to reliable dynamic estimations of transition properties in good agreement with experimental data [26][27][28][29]. Such methodology was previously successfully applied for a large variety of systems, ranging from small gas phase molecules over solvated dyes to dyes occluded in a porous zeolitic environment [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The dominance of the electrostatic contribution to the solvent shift in the n → * electronic excitation has also been observed in the case of acetone. 88,89 Compared to the CCSD predictions, HF is found to give considerably overestimated values for the solvent shift in the n → * electronic transition. Also overestimated are the absolute magnitudes for the excitation energies in gas phase and solution ͑see Tables IV and VI͒.…”
Section: The N \ * Transitionmentioning
confidence: 98%